Growth of Vannamei Shrimp (Litopenaeus vannamei) in Intensive Cultivation Systems - Zakiyyah Nur Inayah; Muhammad Musa; Diana Arfiati (Jurnal Penelitian Pendidikan IPA, 2023)
Vaname shrimp (Litopenaeus vannamei) is one of the shrimps that is widely cultivated in Indonesia. The aim of this research is to analyze the growth and dynamics of water quality in vaname shrimp cultivation ponds using an intensive system. This research is a descriptive study with a survey method conducted in January-April 2023. The research location is in a vaname shrimp cultivation pond with an intensive system with a stocking of 116 individuals/m3. The research results showed that the average weight of shrimp at the end of cultivation was 18.48 grams/fish. Average daily growth ranges from 0.1-0.41 grams. The survival rate (SR) of cultivated vaname shrimp is 75.8% with a feed quantity ratio (FCR) of 1.47. The results of water quality measurements include temperatures ranging from 27.4-30.1 Â°C, brightness 25-65 cm, salinity 21-26 ppt, pH 8-9, dissolved oxygen 4.2-6.7 ppm, carbon dioxide 24.5- 67.1 ppm, ammonia 0.11-1.67, TOM 2.78-108.70 ppm and total vibrio 1x103-3.9x103 CFU/ml. Shrimp growth in ponds is classified as good with water quality suitable for cultivation